The Lord is my shepherd Psalm 23 for the life of the church - Briggs, Richard 1966- (Grand Rapids Baker Academic, 2021)
Offers an exposition of Psalm 23, showing how this classic and beloved text can speak afresh to the life of the church today.
Intro -- Half Title Page -- Series Page -- Title Page -- Copyright Page -- Dedication -- Contents -- Series Preface -- Preface -- Abbreviations -- 1. Introduction -- 2. The World behind Psalm 23 -- 3. The World in Psalm 23 -- 4. The World in Front of Psalm 23 -- 5. Conclusion -- Appendix: Notes: on Psalm 23 in Hebrew -- Bibliography -- Scripture Index -- Subject Index -- Cover Flaps -- Back Cover.
Description based on publisher supplied metadata and other sources
Keywords: Electronic books